Customer Accounting Information And Jordanian Service Companies' Performance: Examining The Role Of Perceived Environmental Uncertainty As A Moderator - Al-Mawali, Hamzah Hussein Khalaf (2012)

(untitled)
This study investigated Customer Accounting (CA) information usage and its impact on the performance of services companies operating in Jordan. It was motivated by the scarcity of the empirical attention given to the subject despite the claimed importance placed by CA promoters. This study sought to substantiate its proposition through four research objectives. First, it aimed to evaluate the extent of CA information usage. The second objective was to identify the level of companies' performance.